Loss of Ezh2 promotes a midbrain-to-forebrain identity switch by direct gene derepression and Wnt-dependent regulation. Issue 1 (December 2015) - Zemke, Martina; Draganova, Kalina; Klug, Annika; Schöler, Anne; Zurkirchen, Luis; Gay, Max; Cheng, Phil; Koseki, Haruhiko; Valenta, Tomas; Schübeler, Dirk; Basler, Konrad; Sommer, Lukas
Abstract Background Precise spatiotemporal control of gene expression is essential for the establishment of correct cell numbers and identities during brain development. This process involves epigenetic control mechanisms, such as those mediated by the polycomb group protein Ezh2, which catalyzes trimethylation of histone H3K27 (H3K27me3) and thereby represses gene expression. Results Herein, we show that Ezh2 plays a crucial role in the development and maintenance of the midbrain. Conditional deletion ofEzh2 in the developing midbrain resulted in decreased neural progenitor proliferation, which is associated with derepression of cell cycle inhibitors and negative regulation of Wnt/β-catenin signaling. Of note, Ezh2 ablation also promoted ectopic expression of a forebrain transcriptional program involving derepression of the forebrain determinants Foxg1 and Pax6. This was accompanied by reduced expression of midbrain markers, including Pax3 and Pax7, as a consequence of decreased Wnt/β-catenin signaling. Conclusion Ezh2 is required for appropriate brain growth and maintenance of regional identity by H3K27me3-mediated gene repression and control of canonical Wnt signaling.